Axillary nerve injury associated with glenohumeral dislocation: A review and algorithm for management. Issue 3 (26th March 2018) - Avis, Duncan; Power, Dominic
Abstract : Axillary nerve injury is a well-recognized complication of glenohumeral dislocation. It is often a low-grade injury which progresses to full recovery without intervention. There is, however, a small number of patients who have received a higher-grade injury and are less likely to achieve a functional recovery without surgical exploration and reconstruction. Following a review of the literature and consideration of local practice in a regional peripheral nerve injury unit, an algorithm has been developed to help identification of those patients with more severe nerve injuries. Early identification of patients with high-grade injuries allows rapid referral to peripheral nerve injury centres, allowing specialist observation or intervention at an early stage in their injury, thus aiming to maximize potential for recovery. Cite this article: EFORT Open Rev 2018;3:70-77. DOI:10.1302/2058-5241.3.170003.